Preparation and Characterization of Cassiterite (Sno2) and Its Application in the Hydrogenation of Methyl Esters - Castro Grijalba, Alexánder; Ramírez, Alfonso; Urresta, Julián; Barrault, Joël (Revista de Ciencias, 2013)
Tin oxide (IV) or cassiterite obtained by the controlled precipitation method was characterized by different physical and chemical techniques such as TEM, surface area, XRD and RTP for the determination of the morphology, particle size distribution and reduction temperature of the system and then, a pure catalyst and doped with tin (Sn) and nickel (Ni) is employed in the hydrogenation of methyl esters from palm oil. Monitoring the reaction was carried out by gas chromatography and it was found that the Sn-doped system showed a higher activity towards hydrogenation. The products obtained during and after the reaction were analyzed by FT-IR. We found that the hydrogenation of double bonds of the carbon chain was the main reaction, but there were also products resulting from isomerization and surprisingly a small fraction of fatty alcohols with tin-based catalyst Sn/SnO2.